Sales, purchases and stock system / Mok Chee Hoe - Mok , Chee Hoe (2001)
Like any other general accounting software, Sales & Purchases Recording System is designed in such a way that it fir into use of different types of organizations. It consists of an accounting database which stores all information regarding the organization’s trading status. Since it should fit to any types of organization, Sales & Purchases Recording System has the capability of allowing multiple users to create their own database files and gain access to them. The software is one of dynamic file allocation in which users can specify and create their own database files. Records inside those files are also of preference of the users. As the software allows multiple users to create their own files, security becomes the main issues. Sales & Purchases Recording System tackles this problem by implementing password protection in which only authorized users can gain access to their files. This is to ensure that the files are kept safe and secure. The software provide features to generate the following accounting modules: Sales Transaction Journal, Purchases Transaction Journal and Inventory Management Modules. All those modules will be automatically generated after the users have closed their accounts. These reports are certainly based on the information of accounts keyed in by users. The software is one with Graphical User Interface (GUI) and is Windows-based application. It provide good interface design with visual clues to help users better understand the software.